Utilizing Twitter to Communicate Risk after a Natural Disaster - Taylor K Ruth; Teresa Suits; Ashley McLeod-Morin; Ricky W Telg (Journal of Applied Communications, 2020)
Hurricane Michael hit the Florida panhandle as a category five hurricane on October 10, 2018. One of the risks after a hurricane is the spread of mosquito-borne disease due to standing floodwaters, which provide perfect breeding grounds for mosquitoes. People often turn to social media during times of crisis to receive up-to-date information. Therefore, there is a need to understand how to use social media to communicate about risks after a natural disaster. The purpose of this study was to explore how Twitter was used to communicate about mosquito control before and after Hurricane Michael and was guided by the Centers for Disease Control’s crisis communication recommendations. Data were collected using Sysomos Media Analytics Platform (MAP). The search included tweets about mosquito control two weeks before and two weeks after Hurricane Michael made landfall and was limited to Florida residents. There were 198 tweets about mosquito control in this timeframe, and a sharp increase in tweets in the weeks following the hurricane. Users tweeting the most about mosquito control were public agencies like mosquito control districts, and common hashtags included #mosquito and #mosquitocontrol; #HurricaneMichael was rarely used. The largest number of tweets were identified with the frame Be First to warn people about mosquito spraying in their local areas. A minority of tweets promoted self-efficacy or promoted action related to mosquito control. None of the analyzed tweets expressed empathy. Extension can use the findings from this study to guide future risk communication on social media following a natural disaster.
Keywords: Risk Communication; Crisis Communication; Natural Disaster; Social Media; Hurricane